Women and Armd Conflict - Javate-De Dios, Aurora (Review of Women's Studies; Vol 25 No 1-2 (2015): Review of Women's Studies Volume XXV, Numbers 1-2 (January-December 2015), 2018)
Strategic Objectives: E1. Increase the participation of women in conflict resolution at decision making levels and protect women living in situations of armed and other conflict or under foreign occupation. E2. Reduce excessive military expenditures and control the availability of armaments. E3. Promote non-violent forms of conflict resolution and reduce the incidence of human rights abuse in conflict situations. E4. Promote women's contribution to fostering a culture of peace. E5. Provide protection, assistance and training to refugee women, other displaced women in need of international protection and internally displaced women. E6. Provide assistance to the women of the colonies and non-self governing territories